Towards high visible light photocatalytic activity in rare earth and N co-doped SrTiO3: a first principles evaluation and prediction. Issue 27 (14th March 2017) - Zhang, Chao; Jiang, Nan; Xu, Shiai; Li, Zheng; Liu, Xingliang; Cheng, Tianle; Han, Aixia; Lv, Haitang; Sun, Wenliang; Hou, Yunlei
Abstract : The band structure and photocatalytic activity of RE (La, Ce, Pr or Nd) mono-doped and RE–N co-doped SrTiO3 for band gap reduction are studied systematically using first principles calculations. Abstract : The band structure and photocatalytic activity of RE (La, Ce, Pr or Nd) mono-doped and RE–N co-doped SrTiO3 for band gap reduction are studied systematically using first principles calculations. Based on the evaluation methods proposed by us previously, various RE–N co-doped cases with La–N, Ce–N, Pr–N and Nd–N co-doped in SrTiO3 are studied. By comprehensive comparison, the favourable co-doping dopants are obtained and the predicted Pr–N co-doped SrTiO3 shows that it may serve as an effective potential candidate photocatalyst for water splitting under visible light among the four types of RE–N co-doped cases. In addition, the f state electrons from the RE atom may have a greater contribution to the band structure narrowing of the RE–N co-doped SrTiO3 .